2006
DOI: 10.3354/meps308279
|View full text |Cite
|
Sign up to set email alerts
|

Differential response in chick survival to diet in least and crested auklets

Abstract: Least auklets Aethia pusilla and crested auklets A. cristatella are abundant planktivorous seabirds found throughout the Bering Sea and are inextricably linked to the secondary productivity of this northern marine ecosystem. We assessed the relationship between productivity and diet in least and crested auklets by examining breeding chronology, daily survival rates (DSR) of chicks, and nestling diet composition at 2 mixed colonies on St. Lawrence Island in the northern Bering Sea during the 2000 to 2002 breedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The capacity to exert such plasticity has been demonstrated for a wide range of other seabird species confronted with environmental change (Golet et al 2000, Hedd et al 2002, Abraham & Sydeman 2004, Gall et al 2006) and has also been demonstrated experimentally for little auks ). Nevertheless, there are indications that foraging conditions of little auks in the eastern part of the Greenland Sea are degrading rapidly.…”
Section: Impacts Of Present Oceanographic Changesmentioning
confidence: 99%
“…The capacity to exert such plasticity has been demonstrated for a wide range of other seabird species confronted with environmental change (Golet et al 2000, Hedd et al 2002, Abraham & Sydeman 2004, Gall et al 2006) and has also been demonstrated experimentally for little auks ). Nevertheless, there are indications that foraging conditions of little auks in the eastern part of the Greenland Sea are degrading rapidly.…”
Section: Impacts Of Present Oceanographic Changesmentioning
confidence: 99%
“…Field data on aspects of least auklet nesting success or the fitness of chicks at St. Paul I. are not available to evaluate the direct effects of shifts in diets. However, at St. Matthew I. in the central Bering Sea, least auklet chicks grew significantly faster when copepods (Calanus marshallae) were abundant in meals brought by adults (Springer et al 1986); there are strong relationships between least auklet demographic parameters and the amount of copepods in chick diets in the Aleutian Islands (Jones & Williams 2007); and at St. Lawrence I. in the northern Bering Sea, the daily survival rate of least auklet chicks was proportional to the amount of copepods in their diets (Gall et al 2006). Work on other species of seabirds has found strong negative correlations between stress and various demographic parameters ).…”
Section: Consequences Of Copepod Anomaliesmentioning
confidence: 99%
“…High levels of nutritional stress reduce reproductive success and survival of adult seabirds, which might have immediate impact on population dynamics . Disappearance of lipid-rich oceanic cope pods from the diets can also impose severe nutritional limitations on growing auklet chicks (Springer et al 1986, Roby 1991, Gall et al 2006, which could increase their post-fledging mortality (Kitaysky et al 2003(Kitaysky et al , 2006. Thus, mediated by the physiological effects of nutritional stress, a warming climate is likely to have a negative impact on planktivores in the productive Green Belt area of the southeastern Bering Sea, as ob served in other areas of the North Pacific (Kitaysky & Golubova 2000, Sydeman et al 2006, Hipfner 2008, Bond et al 2011).…”
Section: Inter-annual Climate Variability Affects Temporal Dynamics Imentioning
confidence: 99%